Assay Suitability for Natural Product Screening: Searching for Leads to Fight Alzheimerʼs Disease - Vasänge, Mervi (Planta Medica, 2014)
Phenotypic and target-based approaches represent two principal strategies for identifying new bioactive compounds. In this review, differences between these approaches, as well as strengths and limitations thereof, are described by examples from the therapeutic area of Alzheimerʼs disease. Some of the central mechanisms of the disease that today are targets of screening campaigns are described. These mechanisms include acetylcholinesterase inhibition, amyloid-based approaches, and oxidative stress. Examples of assays using natural products, either as isolated pure compounds, unpurified or partially purified extracts, are given for each mechanism. Further, the article presents and discusses the pros and cons of both target-based and phenotypic approaches for the chosen mechanisms. In most cases, a thoroughly biology-driven selection of the used assays can be recommended, especially when taking into account the complexity of the disease in question. However, target-based assays also have their justification as long as there is an awareness of what the assay read-out stands for. A clear recommendation is thus for every researcher to critically consider the aim of their bioactivity screening efforts and to adopt the screening strategies most appropriate for the goals set.
Keywords: phenotypic assay; target-based assay; reductionistic; Alzheimerʼs disease; acetylcholinesterase; amyloid; oxidative stress